Strategi Bauran Pemasaran (4P) Terhadap Produk dari Tandan Buah Segar (TBS) Kelapa Sawit Pada PT. Beurata Subur Persada - Wulan Sari; Damrus Damrus (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2021)
Abstract This research aims to find out the marketing mix (4P) strategy for products from Fresh Fruit Bunches (TBS) of palm oil. The study was conducted in April-August 2021. The method used is a qualitative method that is deskrictive with data collection techniques through in-depth interviews, observations, and field studies. As a result of this study, the authors were able to elaborate on the marketing mix strategy towards Fresh Fruit Bunch (TBS) products at PT. Beurata Subur Persada. The recruitment of informants in this study was carried out in two ways, namely the Main Informant and the Supporting Informant consisting of the Main Informant (IU) is the Manager of PT. Beurata Subur Persada, and Supporting Assistants are (IP1) Head of Business Administration, (IP2) Production Admin, and (IP3) Office Admin. The results of this study show that PT. Beurata Subur Persada is a PKS engaged in industry and the management of palm oil TBS into products. The products produced are Crude Palm Oil (CPO), kernel (palm core) and shell. Seeing the essential marketing mix strategy for a company, then PT. Beurata Subur Persada does a plan that is by devising a marketing strategy that aims to anticipate increasingly fierce competition. The strategy in question is a marketing mix strategy that refers to the concept of 4p (product, place and promotion), which with the strategy can realize product survival. Keywords: Marketing Strategy, Marketing Mix and Marketing Mix